Penerapan Uang Kuliah Tunggal (UKT) Perspektif Kaidah Fikih Lā Ḍarar Wa Lā Ḍirār - Devia Anjeli; Kurnaemi Anita; Hijrayanti Sari (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research aims to investigate the establishment of the Single Tuition Fee (UKT) from the perspective of "Lā Ḍarar Wa Lā Ḍirar," utilizing library research methodology with normative and phenomenological approaches. The setting of the Single Tuition Fee in several universities aims to create equal access to higher education by considering the economic capabilities of students and their families. Within the framework of UKT determination, there are various categories that differentiate the amount of UKT to be paid, ranging from the lowest to the highest category, determined by the parents' occupations. From the findings of this research, several cases regarding the establishment of UKT in various universities reveal disparities resulting from interview methods used to determine the UKT amount that are inappropriate and misaligned, causing harm to either the institutions or the students. Therefore, such practices cannot be justified under the Islamic jurisprudential principle of "Lā Ḍarar Wa Lā Ḍirar," which prohibits causing harm to oneself or others. To prevent such issues, it is advisable for institutions to analyze and adopt methods that are precise and target-oriented in determining the UKT, thereby fostering fair and equitable access to higher education.